Os gêneros textuais na aprendizagem inicial da leitura : a provinha Brasil, o livro didático e o professor - Luz, Anne Caroline Silva da (2014)
This dissertation aims at listing and discuss textual genres present in the Evaluation of SCHOOL-AGE CHILDREN, called Provinha Brasil throughout five years of its implementation (2008-2012). This is a correlative study of those documents with the textbook used in the 1st and 2nd years of primary education in municipal schools in Aracaju and also the reflection of these elements in the teaching practice. The present research is based on the National Curriculum Parameters (PCN) - 1st and 2nd cycles of Portuguese Language - , since this document points to a language teaching focused on the text in which the students are able to develop the expertise to adapt their language activities in several social events. The instruments of data analysis were 1. the textual genres present in Provinha Brasil ; 2. 1st and 2nd years textbooks used in municipal schools in Aracaju; 3. Semistructured interviews with two 2nd year teachers of elementary school. The objective of the present research is: i. to map the textual genres found in Provinha Brasil from 2008 to 2012, in order to describe de numerous textual genres presented to students in the beginning of their literacy presented to students in the beginning of their literacy; ii. to analyze the 1st and 2nd textbooks, focusing on aspects of reading and textual genres to point out similarities and differences in approaches to textual genres; iii. to interview 2nd year primary school teachers to check how the professional who are in classrooms comprehend textual genres studies in that year; iv. to establish correlation between PCNs and the instruments of data analysis. It is stressed the importance of working with the textual genres in classroom dealing with its formal and functional aspects. In this regard, the discussions about textual genres are referenced to Marcuschi (2003, 2008, 2010); Bazerman (2005); Souza (2010); Mendonça (2010); Massarini (2007), Rojo (2008). The results obtained through this study were: Provinha Brasil presents great diversity of textual genres, listed 24 different genres; textbooks do not collaborate on the textual genres study to those years of education and are also far from Provinha Brasil multimodal propose; teachers are still insecure about a more promising approach regarding the studies of textual genres to learners reading, and the application of Provinha Brasil needs better instruments of data analysis; PCNs establish a dialogue between Provinha , regarding reading, and textual genres, but there is still much to be done for a more symmetrical balance between the teacher and the textbook.